Impact of the COVID-19 pandemic on tuberculosis control in Indonesia: a nationwide longitudinal analysis of programme data - Surendra, H; Elyazar, IRF; Puspaningrum, E; Darmawan, D; Pakasi, TT; Lukitosari, E; Sulistyo, S; Deviernur, SM; Fuady, A; Thwaites, G; van Crevel, R; Shankar, AH; et al. (Elsevier, 2023)
Background The impact of the COVID-19 pandemic on tuberculosis control in high-burden countries has not been adequately assessed. We aimed to estimate the impact of the COVID-19 pandemic on the national tuberculosis programme in Indonesia, in association with indicators of human development and health-system capacity across all 514 districts in 34 provinces.